The image processing of multi-lens video logging based on Bresenham algorithm - Hongtao Hu; Nana Fu; Zhouli Li (Proceedings (IEEE International Conference on Software Engineering and Service Sciences. Print), 2014)
The wall image of wells acquired by axial lens of multi-lens video logging system has a certain degree of geometric distortion, which is necessary to be corrected to reflect the actual situation of borehole wall. This paper presents an oval image processing method to correct this distortion: firstly, the space coordinate of wall image is transformed from annulus domain to a rectangular domain by using Bresenham algorithm, then the grey scale of each pixel is rebuilt with bilinear interpolation to complete the correction of distorted image. The experimental results show that the proposed method can effectively convert distorted image to a complete rectangular expanded view, improving the accuracy of multi-lens video logging.